التفسير بالرأي بين القبول والرفض - الموسوي, إيمان طالب عبدزيد بنّاي (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The study aims to reveal one of the important types of interpretation, which is interpretation by opinion, and to study the difference in terms of accepting and rejecting this type of interpretation, by making use of the specific rules adopted by scholars and the evidence on which they relied. The study concluded that the sanctity of the Qur’anic text does not mean canceling the role of Reason in interpretation and investigation of purposes. In addition, it is not possible to drag Qur’anic texts into misleading desires that support a certain doctrine, as they take the text into its arena and distance it from its original purposes. The Islamic doctrine derived from the text must be framed with protective factors so that different eyes do not slide into reversing its limited sectarian identity on the absolute infallible text. Despite the existence of orders to prevent interpretation by opinion, some commentators have used this type, and up to the present time we notice those who support it strongly, and it is possible Dealing with this by acquiring the cognitive culture of interpretation, and I addressed this in the research through a preface in explaining the truth of interpretation by opinion, and then followed it with three axes: The first axis deals with the interpretive trends and their multiplicity and the difference in the prohibition and permissibility of interpretation by opinion. The second axis talks about the culture of the interpreter and his goals and their impact on interpretation by opinion. The third axis relates to the opinions of scholars on the relationship between interpretation by opinion and interpretation by ijtihad. The researcher will attempt to clarify these axes and their related details through extrapolation. Analyzing the opinions found in books of interpretation and obtaining results explaining the reasons for its rejection and acceptance.